Innovations in oral hygiene tools: a mini review on recent developments - Palanisamy, Sucharitha (Frontiers in Dental Medicine, 2024)
Background This review examines advancements in oral hygiene aids and their impact on gingival and periodontal health. As periodontal diseases are widespread, effective hygiene is vital. Enhancements in traditional tools and innovations have improved oral hygiene status. Clinical evidence confirms these innovations improve gingival and periodontal health, though proper use and patient adherence are crucial. Methodology A comprehensive literature search was conducted using MeSH terms like “Gingivitis/prevention & control*”, “Dental Plaque/prevention & control*”, “Dentifrices”, “Electrical Equipment and Supplies*”, “Toothbrushing”, “Equipment Design”, “Anti-Infective Agents/therapeutic use”, “Oils, Volatile/therapeutic use”, “Dental Devices, Home Care”, “Dentifrices*/therapeutic use”, “Vibration”, “Gingivitis*/drug therapy”, “Gingivitis*/prevention & control”, “Gingival Hemorrhage/prevention & control”, “Anti-Inflammatory Agents/pharmacology”, “Chlorhexidine/pharmacology”, “Mouthwashes/pharmacology”, “Anti-Bacterial Agents/pharmacology”, “Mouthwashes/therapeutic use”, “Anti-Infective Agents, Local*/therapeutic use”, “Mouthwashes/chemistry*”, “Plant Extracts/therapeutic use*”, “Sodium Dodecyl Sulfate/therapeutic use*”, “Treatment Outcome”, “Oral Hygiene/methods”, “Toothpastes/therapeutic use*”, “Hyaluronic Acid/therapeutic use”, “Chronic Periodontitis*/therapy”, “Periodontal Attachment Loss/therapy”, “Probiotics*/therapeutic use”, “Oral Hygiene*”, “Periodontal Index” and so on. This search utilized PubMed and Google Scholar, restricted to English-language publications from 2018 to 2024. The screening process involved reviewing titles, abstracts, and keywords, focusing on randomized clinical trials only. Inclusion criteria focused on novel innovations in conventional oral hygiene methodologies. A total of 86 randomized clinical trial articles met the inclusion criteria. Results Recent innovations in traditional oral hygiene tools have markedly enhanced oral hygiene levels and patient compliance. These newer innovations demonstrate substantial efficacy in plaque control and gingival health. Clinical outcomes underscore their pivotal role in improving oral hygiene standards, promoting reduced gingivitis and enhanced patient adherence to oral care regimens. Conclusion Advanced oral hygiene aids significantly improve gingival and periodontal health. However, patient adherence and correct usage are crucial for their optimal performance. Incorporating advanced oral hygiene aids into daily practices is essential for achieving optimal periodontal health, and continuous education is necessary to ensure their effective use.